Manifestations of Mythological Formation in the Poetry of Kazem Al-Hajjaj - Fathi Kazem , Assist .Prof. Dr. Hala (Basra studies journal, 2026)
The topic of mythological formation examines the ways in which myth manifests itself in literary and cultural discourse as a symbolic system that reflects both ancient and modern human consciousness of the world, establishing cosmological visions that transcend immediate reality. Mythological formation appears through the invocation of gods, heroes, and supernatural beings, as well as through the re-creation of rituals, symbols, and foundational myths within new narrative and poetic structures. It Is also evident in the use of cyclical time, the conflict between forces of good and evil, and the pursuit of immortality or absolute knowledge. Mythological formation is not limited to the literal transmission of myth; rather, it involves its reinterpretation and deconstruction in accordance with the intellectual and aesthetic vision of the text. Thus, myth becomes an effective tool for constructing meaning, deepening symbolic dimensions, and linking individual experience with collective and cultural memory.